2017
DOI: 10.1155/2017/3517457
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Selected Polycyclic Aromatic Compounds in Particulate Matter Samples with Low Mass Loading: An Approach to Test Method Accuracy

Abstract: A miniaturized analytical procedure to determine selected polycyclic aromatic compounds (PACs) in low mass loadings (<10 mg) of particulate matter (PM) is evaluated. The proposed method is based on a simple sonication/agitation method using small amounts of solvent for extraction. The use of a reduced sample size of particulate matter is often limiting for allowing the quantification of analytes. This also leads to the need for changing analytical procedures and evaluating its performance. The trueness and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Even if the interesting possibilities offered by PLE, particularly in terms of automation, have 374 increased its use over Soxhlet and sonication in recent years, sonication remains one of the 375 most frequent extraction methods. With the "classical solvents" cited in Section 3.1, quantitative extractions of PACs from particulate matters are achieved in less than an hour, even sometimes in less than 20 minutes [32,101,[121][122][123]. According to several works, the extraction recoveries obtained with UAE are similar to those obtained with Soxhlet extraction, but in a far shorter time [32,107,124].…”
Section: Pressurized Liquid Extractionmentioning
confidence: 86%
See 3 more Smart Citations
“…Even if the interesting possibilities offered by PLE, particularly in terms of automation, have 374 increased its use over Soxhlet and sonication in recent years, sonication remains one of the 375 most frequent extraction methods. With the "classical solvents" cited in Section 3.1, quantitative extractions of PACs from particulate matters are achieved in less than an hour, even sometimes in less than 20 minutes [32,101,[121][122][123]. According to several works, the extraction recoveries obtained with UAE are similar to those obtained with Soxhlet extraction, but in a far shorter time [32,107,124].…”
Section: Pressurized Liquid Extractionmentioning
confidence: 86%
“…When keeping the same solvent (dichloromethane), PLE and UAE gave comparable extraction yields. Even if they were slightly favorable to PLE, the authors reported the differences between both extractions as insignificant [121]. These results are presented in Figure 2, where the grey bars represent the quantities of analytes extracted by PLE with dichloromethane, and the darkest bars represent the quantities of analytes extracted by UAE with dichloromethane (abbreviated "AG-D").…”
Section: Pressurized Liquid Extractionmentioning
confidence: 95%
See 2 more Smart Citations